Peran Guru Kristen Sebagai Penuntun di Dalam Kelas [The Role of Christian Teachers as Guides in the Classroom] - Maria Tania Oktaviani Pelita Peda Hella; Grace Purnamasari Christian (Universitas Pelita Harapan, 2022)
The role of the teacher as a guide is expected in leading students in the class, not only in knowledge but also in all aspects of education. The role of a teacher as a guide must be to guide a student to understand and to do the will of the Lord in his or her life. Teachers must be able to guide students to experience the changes and growth that meet the educational purposes. The teacher's role as a guide in performing his or her role requires a student's response in learning. However, the fact is that in learning there are students who participate less actively in the classroom and hinder the learning process. This paper aims to analyse the role of Christian teachers as guides in building students' active participation in the classroom through a literature review. One strategies offered to solve the problem is is through the application of the learning method or media. It could be concluded that the teacher's role as a guide is essential in showing love, leading students to Christ, and encouraging the students’ active participation the goal of learning. The writer's advice for the next researcher is to make direct and thorough research possible so that the teacher can perform his/her role as a guide.BAHASA INDONESIA ABSTRACT: Peran guru sebagai pembimbing sangat diharapkan dalam membimbing murid-murid di kelas, tidak hanya dalam aspek pengetahuan tetapi juga dalam semua aspek pendidikan. Peran guru sebagai pembimbing haruslah membimbing murid untuk mengerti dan melakukan kehendak Tuhan dalam hidupnya. Guru harus dapat membimbing murid untuk mengalami perubahan dan pertumbuhan yang sesuai dengan tujuan pendidikan. Peran guru sebagai pembimbing dalam menjalankan perannya membutuhkan respon siswa dalam belajar. Namun, faktanya dalam pembelajaran terdapat siswa yang kurang berpartisipasi aktif di dalam kelas dan menghambat proses pembelajaran. Makalah ini bertujuan untuk menganalisis peran guru agama Kristen sebagai pemandu dalam membangun partisipasi aktif siswa di dalam kelas melalui kajian literatur. Salah satu strategi yang ditawarkan adalah melalui penerapan metode atau media pembelajaran. Dapat disimpulkan bahwa peran guru sebagai pembimbing sangat penting dalam menunjukkan kasih, menuntun siswa kepada Kristus dan mendorong partisipasi aktif siswa sebagai tujuan pembelajaran. Saran penulis untuk peneliti selanjutnya adalah untuk melakukan penelitian secara langsung dan menyeluruh agar guru dapat menjalankan perannya sebagai pembimbing.